PENERAPAN SADAR WISATA DAN PENGUATAN CITRA WISATA MELALUI PENANAMAAN TANAMAN UPAKARA DI KERAMBITAN KABUPATEN TABANAN - Putri I.A, Trisna Eka; Ariani, N. M. (Buletin Udayana Mengabdi, 2012)
The development of tourism in the area of Kerambitan Village are conducted so conventionally that its development required to pay more attention toward the aspect of environment continuity and also role of society in improving economics. The development of tourism in Kerambitan area have resulted the change toward the cultural and natural environment of society. Potency of Kerambitan Village must be developed with settlement of physical environment and improve the quality of human resource.